2020
DOI: 10.3390/cancers12051287
|View full text |Cite
|
Sign up to set email alerts
|

Older Cancer Patients during the COVID-19 Epidemic: Practice Proposal of the International Geriatric Radiotherapy Group

Abstract: The coronavirus disease 19 (COVID-19) pandemic is unprecedented as it reached all countries in the world within a record short period of time. Even though COVID-19 infection may be just severe in any adults, older adults (65-year-old or older) may experience a higher mortality rate. Among those affected, cancer patients may have a worse outcome compared to the general population because of their depressed immune status. As the health resources of most countries are limited, clinicians may face painful decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 51 publications
0
36
0
2
Order By: Relevance
“…However, some potentially alarming signals of under-treatment were observed and clinical research and scientific activities resulted in being reduced by 80.3% and 80.1%, respectively. Specific guidelines for the treatment of patients with gastrointestinal cancers [ 22 ] and older patients with cancer [ 23 ] were also published. In fact, older cancer patients may be denied supportive care because of their shorter life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, some potentially alarming signals of under-treatment were observed and clinical research and scientific activities resulted in being reduced by 80.3% and 80.1%, respectively. Specific guidelines for the treatment of patients with gastrointestinal cancers [ 22 ] and older patients with cancer [ 23 ] were also published. In fact, older cancer patients may be denied supportive care because of their shorter life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cancer caregivers often have to step up to address patients' healthcare needs and wants [37,[46][47][48][49], which, in turn, could exert substantial mental and physical stress on informal caregivers, above and beyond COVID-19-related burdens the general public shoulders on a daily basis [17][18][19]. Technology-based health solutions can bypass spatial distancing constraints caused by COVID-19 and have the abilities to address unique challenges cancer patients and their caregivers face amid COVID-19 [50][51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary data showed that patients treated with radiation were at high risk of contracting the virus and were more likely to develop a severe form of the illness because of their underlying immunosuppression related to the cancer and various anticancer drugs ( 3 ). According to general radiation guidelines for elderly patients ( 6 , 7 , 8 ), physicians had to take pragmatic actions in order to mitigate the negative effects of the Covid-19 pandemic in a vulnerable population while ensuring tumor control ( 8 ). Most focused on systemic therapies and selected oncology guidelines, especially from the international early recommendations for departments organization and cancer management during COVID-19 pandemic ( 10 ), that served as a framework for the drafting of a protocol for each tumor location in our department.…”
Section: Discussionmentioning
confidence: 99%
“…There is a necessity to allocate specific slots for consultation, simulation CT, and radiation courses for vulnerable patients which requires additional human and material resources. Implementation of protective measures from caretakers and telemedicine practice and other social distancing measures may increase the feeling of abandonment, isolation and incurability ( 6 , 7 ). In addition, in our department a specific workflow dedicated to elderly oncologic patients involving a radiation oncologist with oncogeriatric expertise has been implemented prior the pandemic with time slots and a dedicated visits area.…”
Section: Discussionmentioning
confidence: 99%